ANALYSIS AND DESIGN OF MOBILE WEB-BASED MENU E-ORDER SYSTEMS USING THE PIECES METHOD (CASE STUDY: CAFÉ 50/50 COFFEE) - Nabilah Ananda Pratiwi; Agung Triayudi; Endah Tri Handayani (Jurnal Riset Informatika, 2021)
Café as a place to relax or chatter where visitors can order the menu available. In general, a café often has difficulty in serving customers, especially for menu ordering facilities. This is also experienced by café 50/50 Coffee which still makes menu reservations manually. Based on these problems, a system of e-order menus of web-based mobile applications is designed. The study aims to produce a mobile web ordering system that is then analyzed with the PIECES indicator to determine the level of user satisfaction. Design of this system using the waterfall model System Development Life Cycle (SDLC) development method and then analyzed the level of user satisfaction with the PIECES method. System testing uses usability testing with the USE Questionnaire method. System implementations are created with the help of the CodeIgniter framework and use the PHP programming language. The results of the study in the form of a menu e-order system at the 50/50 Coffee café with the conclusion of the analysis that the users of the e-order system were “SATISFIED”.